Proceedings of the 18th ACM Workshop on Privacy in the Electronic Society 2019
DOI: 10.1145/3338498.3358648
|View full text |Cite
|
Sign up to set email alerts
|

Privacy Protection in Distributed Fingerprint-based Authentication

Abstract: Biometric authentication is getting increasingly popular due to the convenience of using unique individual traits, such as ngerprints, palm veins, irises. Especially ngerprints are widely used nowadays due to the availability and low cost of ngerprint scanners. To avoid identity theft or impersonation, ngerprint data is typically stored locally, e.g., in a trusted hardware module, in a single device that is used for user enrollment and authentication. Local storage, however, limits the ability to implement dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…For example, Shamir Secret Sharing allows the division of the seed phrase and recovery with n out of N parts of the seed phrase [41]. These recovery types can be used as-is or with the help of applications like SeedQuest, FuzzyVault, or the Horcrux Protocol, which help recover seed phrases by playing a game [42], use of biometric data [43], and instantiating Shamir Secret Sharing [44] respectively.…”
Section: Listing 2 a Simple Did Documentmentioning
confidence: 99%
“…For example, Shamir Secret Sharing allows the division of the seed phrase and recovery with n out of N parts of the seed phrase [41]. These recovery types can be used as-is or with the help of applications like SeedQuest, FuzzyVault, or the Horcrux Protocol, which help recover seed phrases by playing a game [42], use of biometric data [43], and instantiating Shamir Secret Sharing [44] respectively.…”
Section: Listing 2 a Simple Did Documentmentioning
confidence: 99%
“…The messages < M 1, M 2, M 4 > are preserved as a hashed value using SHA3, and because of the difficulty of the discrete logarithm problem, inverting the one-way hash function H( •) to retrieve sensitive user information is impossible. While < M 3 > that containsthe locked fuzzy vault information is preserved without hashing but remains secure, it requires the expected attempts of the adversary to interpolate the secret with a precision of approximately 1.86 × 10 9 as calculated in [25]. This corresponds to a 30-bit security level of 1.86 × 10 9 ≈ 2 30 .…”
Section: Privilege Insider Attackmentioning
confidence: 99%
“…Second, it was used to create fuzzy vault sets as an iris extraction algorithm based on the Independent Component Analysis (ICA). In [10], the author suggested that several models for a user be protected as a single entity. A fuzzy vault system was used to derive one multi-biometric template from individual templates.…”
Section: Computer Sciencesmentioning
confidence: 99%
“…This leaves (c s = v s -g s ) pair subsets were containing genuine pairs but include at least one pair of pairs of vaults. If the chaff vault pair is only one member of the candidate sub-set (n+1), the secret polynomial fails because the chaff vault pair does not lie on the secret polynomial [10]. The attacker doesn't know which vault pairs have genuine points, so they can only pick one sub-set, again and again, to interpolate at random.…”
Section: 4 Security Analysismentioning
confidence: 99%